A simplified system for simulation of Streptococcus mutans biofilm on healthy extracted human tooth as dental plaque model - Nadia Halib; Nor Zaihana Abdul Rahman; Nabihah Roslan; Nurhani Jauhar; Rohazila Mohamad Hanafiah (Open Science Publishers LLP Inc., 2024)
Indexed by Scopus